Peranan Penggunaan Transportasi Publik di Perkotaan (Studi Kasus Penggunaan Kereta Commuterline Indonesia Rute Jakarta-Bekasi) - Hendra Wijayanto (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2019)
Public transport is an important means of development for life. The importance of transportation is reflected in the increasing need for transportation services for human mobility and goods as a result of the increasing population growth and the development of settlements in big cities. One type of transportation that can be used as an alternative to overcome the problems of public transportation needs above is the train. Trains that are a means of transportation with many advantages such as low pollution, free of traffic, bulk, cheaper cost, and also save time.With the various advantages possessed by the train above, is expected to be a consideration in order to become an increasingly complex solution of transportation problems in urban areas.